Предмет: Алгебра,
автор: par4i
Упростите выражение:
Приложения:
Ответы
Автор ответа:
0
10m/n(n+m) - (m-n)/m(m+n)=(m²-mn+n²)/mn(m+n)
2)n²/m(m-n)(m+n) + 1/(m+n)=(n²+m²-mn)/m(m-n)(m+n)
3)(m²-mn+n²)/mn(m+n) : (n²+m²-mn)/m(m-n)(m+n)=
=(m²-mn+n²)/mn(m+n) * m(m-n)(m+n)/(n²+m²-mn)=9m-n)/n
2)n²/m(m-n)(m+n) + 1/(m+n)=(n²+m²-mn)/m(m-n)(m+n)
3)(m²-mn+n²)/mn(m+n) : (n²+m²-mn)/m(m-n)(m+n)=
=(m²-mn+n²)/mn(m+n) * m(m-n)(m+n)/(n²+m²-mn)=9m-n)/n
Автор ответа:
0
Спасибо!
Похожие вопросы
Предмет: Математика,
автор: ademi8811
Предмет: Русский язык,
автор: lavacreep83
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: СоняСкупнова
Предмет: Литература,
автор: SvetlanaBragina